State-of-the-art on monolingual lexicography for Brazil (Brazilian Portuguese) - Tanara Zingano Kuhn (Slovenščina 2.0: Empirične, aplikativne in interdisciplinarne raziskave, 2019)
This paper is a minireview of the current status of monolingual lexicography in Brazil. Firstly, a brief contextualization of the origins of Brazilian Portuguese dictionary-making is provided. Then, an account of contemporary monolingual dictionaries is given and a more detailed overview on print, digital, spelling, and school dictionaries is presented. Next, research into dictionary use is reviewed. Finally, the perception among the Brazilians with regards to corpora and use of crowdsourcing in lexicography is discussed.